PENINGKATKAN PEMAHAMAN DAN KEMAMPUAN PESERTA DIDIK PADA MATERI PEMBELAJARAN IMAN TERHADAP HARI AKHIR BIDANG STUDI PENDIDIKAN AGAMA ISLAM KELAS IX-1 DI SMP NEGERI 24 BANDAR LAMPUNG - Antoni, Marlin (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The objective of this research is to improve the students‟ learning outcomes in the learning materials on the end of faith study of islamic religious education at the tenth grade students in SMP Negeri 24 Bandar Lampung using demonstrative method. This study is classroom action research. The participants come from the tenth grade students in SMP Negeri 24 Bandar Lampung. After doing a research, it is found that the development of the understanding and ability of learners in the learning materials in relation in the field of Islamic education studies also implied in full in the results such as the ability and resolve operational in relation skills using varied demonstration properly.